Synthesis, crystal structures, and magnetic properties of three new iron(II) complexes with pyrrolyl-substituted triaryltriazoles. Issue 18 (16th September 2016) - Li, Bin; Zhou, Yong-Fei; Zhang, Shi-Pei; Qin, Tao; Shen, Xuan; Xu, Yan; Zhu, Dun-Ru
Abstract: Three pyrrolyl-substituted triaryltriazoles, 3-( N -methyl-2-pyrrolyl)-4-( p -R-phenyl)-5-(2-pyridyl)-1, 2, 4-triazole (L 1 : R = MeO; L 2 : R = Cl; L 3 : R = Br), and their mononuclear iron(II) complexes, trans -[Fe(L 1–3 )2 (NCS)2 ]∙2MeOH (1 : L 1 ;2 : L 2 ;3 : L 3 ), have been synthesized and characterized by elemental analysis, FT-IR, ESI-MS, and single-crystal X-ray crystallography. Crystallographic studies revealed that1 –3 are isomorphous and crystallize in the triclinic space group P -1. All the complexes have a similar octahedral [FeN6 ] core with two trans -NCS − ions. Each ligand adopts a chelating bidentate coordination mode via the pyridyl N and one N of the triazole. Intermolecular O–H⋯O hydrogen bonding and C–H⋯ π interactions link the molecules of1 –3 to form a 1-D chain or 2-D framework. Variable-temperature magnetic susceptibility measurements indicated that all the complexes remained in a high-spin state from 1.8 to 300 K and had a weak antiferromagnetic interaction. Graphical Abstract: